Cultural factors influencing higher education achievement: A comparative study of Batak, Minang, and Javanese societies in Indonesia - Surata, I Ketut; Winaya, Ni Nyoman Teristiyani; Wahyuni, Luh Mei (Journal of Language, Literature, Social and Cultural Studies, 2025)
This study aims to examine the relationship between ethnicity and educational attainment in Indonesia, specifically focusing on the Batak, Minangkabau, and Javanese communities. By analysing the factors contributing to their educational success, the research seeks to highlight the role of cultural values, historical context, and socio-economic factors in shaping the academic achievements of these ethnic groups. The research employs a qualitative approach, utilizing a document study method to analyse data from the Badan Pusat Statistik (BPS, 2024) and other relevant sources. This method involves reviewing published reports and statistical data from 2024 that outline the educational attainment of various ethnic groups in Indonesia. The study focuses on comparing the number of graduates from Batak, Minangkabau, and Javanese communities, considering factors such as population size, access to education, and socio-cultural influences. The findings suggest that the Batak and Minangkabau communities, despite being from less populous regions, have achieved remarkable success in higher education. The Batak’s emphasis on intellectual and social success, along with their cultural focus on maintaining family honour and wealth, plays a key role in motivating higher education pursuits. In contrast, the Javanese community, despite better access to education, lags behind in terms of the percentage of university graduates. This study concludes that cultural factors such as value systems, traditions, and social norms are significant drivers of educational success. By focusing on the promotion of education within families and communities, ethnic groups can contribute significantly to Indonesia's national educational advancement. The research suggests that increased focus on education in all ethnic communities can lead to greater educational equity in Indonesia.